2015
DOI: 10.1095/biolreprod.114.126474
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Gene Dosage of Tfap2c Impairs Trophoblast Lineage Differentiation and Alters Maternal Blood Spaces in the Mouse Placenta1

Abstract: Tfap2c is required for placental development and trophoblast stem cell maintenance. Deletion of Tfap2c results in early embryonic loss because of failure in placental development. We evaluated the effect of reduced Tfap2c expression on fetal outcome and placental development. Sixty percent of the heterozygous mice were lost directly after birth. Labyrinthine differentiation was impaired, as indicated by enhanced proliferation and inclusions of cobblestone-shaped cell clusters characterized by expression of Tfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…We identified a substantial fraction of transcriptional repressors ( IKZF5 , IFI16 , BHLME40 and CBFA2T2 ), genes associated with DNA mismatch repair ( PMS1 and MBD4 ), and several components of NFκβ ( BCL3 and RELA ) and WNT ( CDX1 , HBP1 and HMGN3 ) signalling pathways. Interestingly, the network also contained TFAP2C and GCM1 , which in mouse are associated with trophoblast lineage specification ( Kaiser et al, 2015 ; Sharma et al, 2016 ) and regulation of syncytium formation ( Kashif et al, 2011 ; Lu et al, 2016 ), respectively. For quantitative visualisation of species specificity, we plotted relative expression of transcription factors and epigenetic modifiers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a substantial fraction of transcriptional repressors ( IKZF5 , IFI16 , BHLME40 and CBFA2T2 ), genes associated with DNA mismatch repair ( PMS1 and MBD4 ), and several components of NFκβ ( BCL3 and RELA ) and WNT ( CDX1 , HBP1 and HMGN3 ) signalling pathways. Interestingly, the network also contained TFAP2C and GCM1 , which in mouse are associated with trophoblast lineage specification ( Kaiser et al, 2015 ; Sharma et al, 2016 ) and regulation of syncytium formation ( Kashif et al, 2011 ; Lu et al, 2016 ), respectively. For quantitative visualisation of species specificity, we plotted relative expression of transcription factors and epigenetic modifiers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To develop a cell culture-based system for further analyses of this deletion, we established trophoblast stem cell (TSC) lines from blastocysts carrying a maternally or paternally inherited Del 7AI allele. Ascl2 levels peak between days 1 and 3 of TSC differentiation induced by FGF4 withdrawal [ 18 , 21 , 37 40 ]. Furthermore, RNA-seq profiling of hybrid TSC lines showed that Ascl2 is already imprinted in undifferentiated TSCs, with more than 90% of expression coming from the maternal allele [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified a substantial fraction of transcriptional repressors (IKZF5, IFI16, BHLME40 and CBFA2T2), genes associated with DNA mismatch repair (PMS1, MBD4) and several components of NFκβ (BCL3, RELA) and WNT (CDX1, HBP1, HMGN3) signalling pathways. Interestingly, the network also contained TFAP2C and GCM1, which in mouse are associated with trophoblast lineage specification (Kaiser et al, 2015;Sharma et al, 2016) and regulation of syncytium formation (Kashif et al, 2011;Lu et al, 2016), respectively. For quantitative visualisation of species specificity we plotted relative expression of transcription factors and epigenetic modifiers ( Fig.…”
Section: Conserved and Primate-specific Elements Of The Epi And Pre Tmentioning
confidence: 99%